ANA Serum in a Non-Human Primate (Macaca fascicularis) Model of Systemic Lupus Erythematosus Induced by Pristane - Jonny, Jonny; Zenia, Pepita; Kusumastuti, Sanindita; Wirjopranoto, Soetojo; Nidom, Chairul Anwar; Sudiana, I Ketut; Pratiwi, Elisa Diah; Mawaddah, Tiza Wuri; Nidom, Astria Novitasari; Nidom, Reviany Vibrianita; Indrasari, Setyarina; Rosytania, Irma Yurita (Trends in Immunotherapy, 2026)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease characterized by the production of antinuclear antibodies (ANA). While murine models are widely used for lupus research, their translational value is limited by physiological differences. Macaca fascicularis, a non-human primate, offers a closer model due to its genetic and immunological similarities to humans. Pristane (2,6,10,14-tetramethylpentadecane), a hydrocarbon oil, can induce lupus-like manifestations, including ANA production, but evidence in Macaca fascicularis remains scarce. This study assessed ANA titers following pristane induction in seven macaques, with one serving as a negative control. A single intraperitoneal dose of pristane (5 mL/kg) was administered, and ANA titers were evaluated biweekly using ELISA. ANA seropositivity (titer ≥1:80) was first detected at week 4, increasing to four macaques by week 8 and persisting at four positives in week 10. The duration of ANA positivity varied across individuals, ranging from a single week to continuous six-week responses, with one showing a biphasic pattern. The control macaque remained negative throughout. Clinical observations included alopecia, weight loss, lymphopenia, hematuria, and proteinuria in ANA-positive animals. In conclusion, pristane induced measurable autoimmunity in Macaca fascicularis, supporting its utility as a translational model for lupus research and preclinical testing of therapeutic interventions.